Hesapsal kişilik kavramı - (:unkn) unknown (My University, 2012)
Hesapsal Kişilik, teşebbüslerde hesap dengesini kuran, temsil eden ve yöneten bir kişiliktir. Bu kişilik; hukuktaki kişilerden, gerçek ya da tüzel kişi sahiplerden veya kurumun borçlu olduğu kişilerden farklı olan, bağımsız kararlar verebilmek üzere belirli bir dönem için yetki ve sorumluluk verilmiş bir kişiliktir. Hesapsal Kişilik Kavramına göre, teşebbüsün sahibi olan kişi kendi kurduğu işletmede,2.Hesapsal Kişidir ama onun tayin ettiği kişi, 1.Hesapsal Kişi olarak kurumu yönetebilmektedir. Bu Kavramla işletme sahibinin hesapları ile işletmenin kendi hesapları birbirinden kesin olarak ayrılabilmektedir.

Accounting entity is an entity which balances, represents and manages the accounts in an enterprise. Unlike real person, legal person or persons to whom the corporation is indebted this entity is the personality who has been given the power and responsibility to make independent decisions during a certain period of time. According to the accounting entity concept, the owner of the business is the second accounting entity in the organization he has founded but the person he has appointed can manage the business as the first accounting entity. The concept of accounting entity definitely separates the accounts of the business and the accounts of the owner.
The concept of accounting entity
Keywords: İktisat; İşletme